Behavioral additionality: The role of cooperation with research institutions in fostering technological maturity of enterprises - Arkadiusz Michał Kowalski; Marta Mackiewicz (International Journal of Management and Economics, 2022)
The main aim of the article is to examine how cooperation with research institutions influences technological maturity of enterprises. It is accompanied with the additional aim, which is to assess the role of innovation policy interventions in this process, as captured by the concept of behavioral additionality, which is one of the externalities of public support for R&D. The focus of this article is put on one of the specific types of behavioral additionality-cooperation additionality-which takes place in the situation where public support influences the collaboration behavior of a firm receiving R&D support. The study was conducted with the use of firm-level data collected in a survey on the sample of 464 enterprises operating within national smart specializations in Poland. The results of the research suggest that public funding fosters the cooperation between scientific institutions and enterprises, thus confirms the cooperation additionality.
Keywords: O31; O36; O14; 650; behavioral additionality; cooperation; cooperation additionality; innovation; research institutions; technological maturity